On a European collaboration to identify organizational models, potential shortcomings and improvement options in out-of-hours primary health care - Leutgeb, Rüdiger; Walker, Nicola; Remmen, Roy; Klemenc-Ketis, Zalika; Szecsenyi, Joachim; Laux, Gunter (European journal of general practice, 2014)
Background: Out-of-hours care (OOHC) provision is an increasingly challenging aspect in the delivery of primary health care services. Although many European countries have implemented organizational models for out-of-hours primary care, which has been traditionally delivered by general practitioners, health care providers throughout Europe are still looking to resolve current challenges in OOHC. It is within this context that the European Research Network for Out-of-Hours Primary Health Care (EurOOHnet) was established in 2010 to investigate the provision of out-of-hours care across European countries, which have diverse political and health care systems. In this paper, we report on the EurOOHnet work related to OOHC organizational models, potential shortcomings and improvement options in out-of-hours primary health care.Needs assessment: The EurOOHnet expert working party proposed that models for OOHC should be reviewed to evaluate the availability and accessibility of OOHC for patients while also seeking ways to make the delivery of care more satisfying for service providers.Outcomes: To move towards resolution of OOHC challenges in primary care, as the first stage, the EurOOHnet expert working party identified the following key needs: clear and uniform definitions of the different OOHC models between different countries; adequate—ideally transnational—definitions of urgency levels and corresponding data; and educational programmes for nurses and doctors (e.g. in the use of a standardized triage system for OOHC). Finally, the need for a modern system of data transfer between different health care providers in regular care and providers in OOHC to prevent information loss was identified.